Mawduʿ Hadith in the Digital Landscape: Epistemic Challenges and Contemporary Islamic Literacy - Dakhirotul Ilmiyah; Md Noor Hussin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Abstract This study examines the phenomenon of mawdu’ (fabricated) hadith in the digital landscape as an epistemic challenge to contemporary Islamic literacy. While digital transformation has greatly expanded access to hadith sources, it has simultaneously facilitated the rapid circulation of unverified religious content that often deviates from established scholarly methodologies. Employing a qualitative approach, this research combines a systematic literature review with limited observational analysis of digital religious content. Classical and contemporary literature on mawdu’ hadith, Ulum al-Hadith, and digital Islamic literacy are systematically analyzed to construct an epistemic framework for analysis. Illustrative empirical data was obtained through observation of hadith content circulating on social media platforms, particularly TikTok and Instagram, where hadith are often disseminated without scrutiny of their sanad, explanation of their quality, or consideration of their historical context. The research findings show that social media has become a new ecosystem in which the authority of hadith is determined more by algorithmic visibility than by scholarly verification. Low levels of digital Islamic literacy contribute significantly to the uncritical acceptance of fabricated hadith. This study confirms that comprehensive digital Islamic literacy is an important prerequisite for maintaining epistemic integrity and ensuring the responsible transmission of hadith in the digital age. Abstrak Penelitian ini mengkaji fenomena hadis mawdu’ (hadis palsu) dalam lanskap digital sebagai tantangan epistemik bagi literasi Islam kontemporer. Meskipun transformasi digital telah sangat memperluas akses terhadap sumber-sumber hadis, pada saat yang sama ia juga memfasilitasi peredaran cepat konten keagamaan yang tidak terverifikasi dan sering terlepas dari metodologi keilmuan yang mapan. Dengan menggunakan pendekatan kualitatif, penelitian ini mengombinasikan tinjauan kepustakaan sistematis dengan analisis observasional terbatas terhadap konten keagamaan digital. Literatur klasik dan kontemporer tentang hadis mawdu’, Ulum al-Hadith, dan literasi Islam digital dianalisis secara sistematis untuk membangun kerangka epistemic analisis. Data empiris ilustratif diperoleh melalui pengamatan terhadap konten hadis yang beredar di platform media sosial, khususnya TikTok dan Instagram, di mana hadis sering disebarluaskan tanpa penelaahan terhadap sanad-nya, tanpa penjelasan mengenai kualitasnya, atau tanpa mempertimbangkan konteks historisnya. Temuan penelitian menunjukkan bahwa media sosial telah menjadi sebuah ekosistem baru di mana otoritas hadis lebih banyak ditentukan oleh visibilitas algoritmik daripada verifikasi keilmuan. Rendahnya tingkat literasi Islam digital berkontribusi secara signifikan terhadap penerimaan hadis palsu secara tidak kritis. Penelitian ini menegaskan bahwa literasi Islam digital yang komprehensif merupakan prasyarat penting untuk menjaga integritas epistemik dan memastikan transmisi hadis yang bertanggung jawab di era digital.